Emotional Intelligence of Undergraduate Athletes: The Role of Sports Experience - Rodriguez-Romo, Gabriel; Blanco-Garcia, Cecilia; Diez-Vega, Ignacio; Acebes-Sánchez, Jorge (Frontiers in Psychology, 2021)
Sport is an emotional experience. Studies have shown that high emotional intelligence (EI) is associated with better sports performance although different aspects of sports experience and their relationship with EI are still unclear. This study examined the possible relationships between sports experience and EI dimensions of undergraduate athletes. Likewise, according to the differences described in the literature between men and women, the secondary aim was to identify the possible relationship between EI and sports experience in both subgroups. A total of 1784 [712 men (39.9%), 1072 women (60.1%); mean age = 21.3 years, SD = 4.2)] undergraduate athletes completed the Trait Meta Mood Scale and a sports experience questionnaire. Comparisons between groups were performed using Mann–Whitney-U and H-Kruskal Wallis tests and correlations between variables were analyzed using Spearman correlation. We found that the number of different sports practiced and the number of years practicing sports were positively associated with emotional repair (ER). However, the number of years practicing sports was negatively associated with emotional attention (EA). Male athletes who trained more and had a higher competitive level were more likely to show higher ER. In any case, it is necessary to take into account that all the associations were weak. Our study suggested that athletes tend to attend to and value their feelings, and use positive thinking to repair their negative moods.